2017
DOI: 10.1192/bjp.bp.117.199331
|View full text |Cite
|
Sign up to set email alerts
|

When unbearable suffering incites psychiatric patients to request euthanasia: qualitative study

Abstract: BackgroundThe concept of ‘unbearable suffering’ is central to legislation governing whether euthanasia requests may be granted, but remains insufficiently understood, especially in relation to psychiatric patients.AimsTo provide insights into the suffering experiences of psychiatric patients who have made a request for euthanasia.MethodTestimonials from 26 psychiatric patients who requested euthanasia were analysed using QualiCoder software.ResultsFive domains of suffering were identified: medical, intraperson… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
99
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(106 citation statements)
references
References 20 publications
3
99
0
4
Order By: Relevance
“…Furthermore, the authors of a qualitative analysis of the same population remarked on the significance of how much planning took place in advance of these deaths. They reported that those eligible for euthanasia partook in “advance preparation of all kinds of financial and practical arrangements, from the preparation of a warm and serene atmosphere in which the act of euthanasia would take place at home, to making sure that the act of euthanasia would not take place near or during holiday seasons.” 22 …”
Section: Impulsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the authors of a qualitative analysis of the same population remarked on the significance of how much planning took place in advance of these deaths. They reported that those eligible for euthanasia partook in “advance preparation of all kinds of financial and practical arrangements, from the preparation of a warm and serene atmosphere in which the act of euthanasia would take place at home, to making sure that the act of euthanasia would not take place near or during holiday seasons.” 22 …”
Section: Impulsivenessmentioning
confidence: 99%
“…A qualitative analysis of people who requested assistance in dying in Belgium for psychological suffering found that “suicide in general was considered as painful, horrific and humiliating, but still evaluated as a possibility by patients whose euthanasia requests could not be granted. However, dying in a caring environment, surrounded by loved ones, was very much the preferred option.” 69 …”
Section: Beyond a Fundamental Differencementioning
confidence: 99%
“…As Hall & Parker note, the legislative criteria for euthanasia differ between countries and have expanded over time. Some jurisdictions require a diagnosis of an incurable illness, whereas others allow euthanasia for ‘untreatable’ and ‘unbearable’ suffering . We argue that the way in which these criteria are interpreted by those with the legal authority to assess euthanasia requests tells us much about how addiction is being conceptualized.…”
mentioning
confidence: 97%
“…For example, some mental health researchers (e.g. worry about the impact of poverty on people experiencing mental health issues, and the difficulty of disentangling this from other factors when considering the suffering cited in requests for euthanasia for mental illness.…”
mentioning
confidence: 99%
“…The vast majority of these requests have a somatic cause; a psychiatric reason was reported in 1% or fewer of the cases in each year [2]. A complicating factor is that in these cases, various symptoms converge: "Psychiatric patients do not only suffer from psychological symptoms, but also from general and specific physical and/or psychosomatic symptoms" [3]. Belgium, too, shows an increase in psychiatric euthanasia cases [4].…”
mentioning
confidence: 99%